2004
DOI: 10.1074/jbc.m308688200
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin-mediated Anticoagulant Activity of Sulfated Polysaccharides

Abstract: We investigated the mechanisms of anticoagulant activity mediated by sulfated galactans. The anticoagulant activity of sulfated polysaccharides is achieved mainly through potentiation of plasma cofactors, which are the natural inhibitors of coagulation proteases. Our results indicated the following. 1) Structural requirements for the interaction of sulfated galactans with coagulation inhibitors and their target proteases are not merely a consequence of their charge density. 2) The structural basis of this inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 46 publications
8
108
0
Order By: Relevance
“…With the examples described throughout the text, it is clear that the template mechanisms between SP (SF, SG, GAG), serpins (AT, HC-II) and protease (IIa) have differential stabilities or formation kinetics that are directly related to the structural features of the SP. and fully supports the expected bridging mechanism for the activity of SG, as previously described (Melo et al, 2004). Thus, both compounds are capable of interacting with AT, as indicated by theoretical results and experimental data showing that both polysaccharides are retained on an AT-affinity column.…”
Section: Preferential Conformation Binding-dependent Casesupporting
confidence: 59%
See 1 more Smart Citation
“…With the examples described throughout the text, it is clear that the template mechanisms between SP (SF, SG, GAG), serpins (AT, HC-II) and protease (IIa) have differential stabilities or formation kinetics that are directly related to the structural features of the SP. and fully supports the expected bridging mechanism for the activity of SG, as previously described (Melo et al, 2004). Thus, both compounds are capable of interacting with AT, as indicated by theoretical results and experimental data showing that both polysaccharides are retained on an AT-affinity column.…”
Section: Preferential Conformation Binding-dependent Casesupporting
confidence: 59%
“…Anticoagulant activities of MSPs measured by APTT a and by IC50 for thrombin (IIa) and factor Xa inhibition in the presence of antithrombin (AT) or Heparin Cofactor II (HCII) (Pavão et al, 1998;Mourão, 2004;Pereira et al, 2005;Fonseca et al, 2008 Pavão et al, 1998. complex between heparin-AT-IIa ( Figure 4A), which supports the potentiation of this protease inactivation by AT in the presence of SG. This is an example of how the orientational constraints in solution can influence spatial preferences of the SP for their different bindings with target proteins (Melo et al, 2004). It is obvious that the difference in the sugar type drastically changes the conformation of the polymer as well, implying a different conformational binding, as explained in this section.…”
Section: Preferential Conformation Binding-dependent Casementioning
confidence: 99%
“…The results of anticoagulant activity indicated that the increasing of sulfate content from 15.04 % for UR to 25.68 % for URS resulting in an increasing of bioactivity. Melo et al [13] reported that the introduction of sulfate to polysaccharides increases the amount of negative charge. Then, the negatively charged sulfate groups can be combined with the positively charged groups from the coagulation protease inhibitor antithrombin, which can activate antithrombin and produce anticoagulant activity.…”
Section: Resultsmentioning
confidence: 99%
“…The results of 1 H và 13 C-NMR analysis were summarized in Table 1. The presence of sulfate groups after sulfation process was confirmed by FTIR and NMR spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the incidence of prion-related diseases in cows means that bovine heparin runs a risk of contamination which has to be carefully monitored. In the meantime, the ever-increasing demand for antithrombotic therapy calls for alternative sources of anticoagulant and antithrombotic compounds [8]. It has been shown that sulfated polysaccharides with anticoagulant activity are most abundant in marine invertebrates and marine algae [9,10].…”
Section: Preparation and Characterization Of Abalone Gonad Polysacchamentioning
confidence: 99%